Strategi Kampanye Di Era Digital: Dengan Memanfaatkan Aplikasi X Dalam Pemilu 2024 - Aggi Nurhapipah; Shiva Steviana; Reza Mauldy Raharja (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Social media has become a tool for political campaigns, one of which is in the 2024 general election which uses the X application as a force to get people’s votes. Social media refers to internet platforms such as blogs and networks where people can engage, share and generate information easily. The X application or Twitter is a social media platform that facilitates users in writing or tweeting containing short messages that can be shared by anyone on Twitter or the X application. This application only supports images, videos or text. This research aims to explore campaign strategies in the digital era by utilizing the X application in the 2024 election. The focus of the research is on how the X application influences voter participation and its influence on public opinion. The research method used is a qualitative method based on secondary data. It is hoped that this research can provide a deeper understanding of the role of the X application in the democratic and political process in the digital era.